Effects of sputum on pulmonary function. Issue 6096 (5th November 1977) - Cochrane, G M; Webber, B A; Clarke, S W
Abstract : The specific airways conductance (SGAW) of 23 patients with copious sputum production and airflow obstruction was measured before and after physiotherapy to determine the effect of bronchial secretions on pulmonary function. Chest physiotherapy to remove these secretions had the effect of reducing airflow obstruction, as measured by SGAW. These findings suggest that sputum has a detrimental effect on pulmonary function and that physiotherapy can reduce airways obstruction.